THE IMPROVING BY USING OF VISUAL MEDIA APPROACH IN THE ENGLISH LANGUAGE LISTENING SKILLS AT CLASS X AK.2 SMKN 3 WAJO - Husni, Andi; Maisanto, Antoni; Sitorus, Budianto; Nurlelalah, Andi; Uleng, Besse; Muktar, Andi Ronal (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
Results of research on the use of visual-Media to improve listening skills in student of class X AK.2 SMKN 3 Wajo, concluded that students' listening skills can be increased through the use of visual-Media learning. Listening skills of students in the first cycle in the category enough to average 68.71, and yet meet the expected learning completeness, then the second cycle increased to excellent category with an average of 83.87, and has met the expected learning completeness. Increasing listening skills through the use of visual-Media is supported by the increase in student learning activities, such as: active students prepare themselves in the content of chert listening to visual-Media, listen to the story in the visual-Media, noted the contents of the story, questioning related to the content of the story, and concluded the material content of the story on visual-Media.